(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
For maintenance of the technological process, control and ecological assesment it is necessary to perform an estimate of environmental aspects that could have a sensible impact to environment. Environmental aspects and its impact is analyzed in the report. In the report is developed: 1. Friendly to environment technological scheme for production of wood poles for power lines. 2. Principial scheme and models o f hazard estimate 3. Hazard charts for the environmental defence 4. Algorithm of estimate of ecological for the environment That depends o f the problem’s topicality and enumeration of the hazard factors the specific problems solutions are offered that allow to controlthe manyfacturing process from the view of allowance need related to environmental defence.